2000
DOI: 10.1111/j.1752-0606.2000.tb00272.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Theory in Family Therapy Research: A Content Analysis of Family Therapy Journals

Abstract: Ninety-five studies from Family Process and Journal of Marital and Family Therapy were evaluated with regard to their use of theory. While a majority of the articles were judged to use theory in either an explicit or an implicit manner, 42% did not appear to draw on theory in either the introductory or discussion sections. Studies that used qualitative methods appeared to use theory more frequently and explicitly than those using quantitative methods alone. Systems theory was found to be the most common concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 6 publications
2
36
0
Order By: Relevance
“…The clear majority of articles employed quantitative methods (94%). However, qualitative method articles in Taylor and Bagd's (2005) analysis used theoretical frameworks more frequently, consistent with Hawley and Geske's (2000) finding.…”
Section: Completed)supporting
confidence: 71%
See 4 more Smart Citations
“…The clear majority of articles employed quantitative methods (94%). However, qualitative method articles in Taylor and Bagd's (2005) analysis used theoretical frameworks more frequently, consistent with Hawley and Geske's (2000) finding.…”
Section: Completed)supporting
confidence: 71%
“…This finding, coupled with that of Lavee and Dollahite (1991), suggests that articles employing theory to frame research in the introduction/literature review and then extending or applying theory in the discussion were the exception, not the rule. Hawley and Geske (2000) concluded that the theory-research link is an ideal, but is lacking in empirical investigations in the family therapy field.…”
Section: Completed)mentioning
confidence: 99%
See 3 more Smart Citations